Dampak Penggunaan Teknologi terhadap Karakter Peserta Didik di SMP Negeri 4 Lahewa Timur - Tris Desniat Natalia Hulu; Melvan Nastuti Nazara; Agnes Renostini Harefa (Journal on Education, 2023)
Education is an activity that is carried out in guiding and directing someone. With education, it can also humanize humans in a better direction as it exists and we can see at this time. That the more technology develops, the less character patterns possessed by today's children. This research is a qualitative research using a descriptive approach. Based on the results and data obtained, it is concluded that student character can be influenced by the use of technology. after examining how student character is affected by the use of technology (gadgets). Some of the solutions the authors can offer include: 1) It is hoped that students will use fewer gadgets in order to increase children's self-control and prevent them from playing too much with gadgets which can later interfere with children's mental and physical health. 2) It is expected that parents can control and limit the use of gadgets by their children by controlling how long they play with these gadgets. 3) It is hoped that teachers can teach students about the dangers of excessive use of gadgets and can also show students how to use gadgets correctly, one of which is by using them as learning tools.